SYA 013 analogs as sigma-2 (σ(2)) selective ligands: structure-affinity relationship studies - Al-Ghanim, Lamya (Bioorg Med Chem, 2019)
Several lines of evidence suggest that selective sigma-2 (σ(2)) ligands might be useful for the treatment of solid tumors. However, very few selective σ(2) ligands have been identified. This study was aimed at identifying new selective σ(2) receptor ligands using a previously identified agent, SYA 013 as a lead. Four groups, homopiperazine, piperazine, tropane and selected oxime analogs of the homopiperazines were identified, synthesized and subsequently screened at the σ(1) and σ(2) receptors. The results demonstrate that these scaffolds can be modified to obtain selective σ(2) receptor ligands. 1-(5-Chloropyridin-2-yl)-4-(3-((4-fluorophenyl)thio)propyl)-1,4-diazepane, 7 and 3-(4-chlorophenyl)-8-(3-((2-fluorophenyl)thio)propyl)-8-azabicyclo[3.2.1]octan-3-ol, 21 were identified as the highest binding affinity ligands (σ(2)Ki=2.2 nM) and (4-(4-(5-chloropyridin-2-yl)-1,4-diazepan-1-yl)-1-(4-fluorophenyl)-butan-1-one oxime, 22 as a high affinity and the most selective ligand for the σ(2) receptor (σ(1)Ki/σ(2)Ki = 41.8).